2017
DOI: 10.4269/ajtmh.16-0170
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Household- and Community-Level Sanitation and Fecal Sludge Management on Urban Fecal Contamination in Households and Drains and Enteric Infection in Children

Abstract: Urban sanitation necessitates management of fecal sludge inside and outside the household. This study examined associations between household sanitation, fecal contamination, and enteric infection in two low-income neighborhoods in Vellore, India. Surveys and spatial analysis assessed the presence and clustering of toilets and fecal sludge management (FSM) practices in 200 households. Fecal contamination was measured in environmental samples from 50 households and household drains. Enteric infection was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 53 publications
(85 reference statements)
0
26
0
Order By: Relevance
“…While further research is needed to substantiate this observation, it may reflect the poor containment of faeces from these toilets. Owning and using toilets that discharged to open drains may have been of limited benefit during periods of heavy monsoon or flooding because of the high levels of human‐specific faecal contamination discharged into the immediate environment . Previous cross‐sectional evidence from this population has shown that children in households with toilets that discharged to open drains had the highest prevalence of enteric infection, even compared to those in households without toilets, suggesting that contamination of the immediate environment may have reduced the health benefits associated with toilet ownership .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…While further research is needed to substantiate this observation, it may reflect the poor containment of faeces from these toilets. Owning and using toilets that discharged to open drains may have been of limited benefit during periods of heavy monsoon or flooding because of the high levels of human‐specific faecal contamination discharged into the immediate environment . Previous cross‐sectional evidence from this population has shown that children in households with toilets that discharged to open drains had the highest prevalence of enteric infection, even compared to those in households without toilets, suggesting that contamination of the immediate environment may have reduced the health benefits associated with toilet ownership .…”
Section: Discussionmentioning
confidence: 94%
“…Annually, Vellore has a dry season (January–May), a southwest monsoon (June–September) and a northeast monsoon (October–December) . Old Town is a small, low‐income urban neighbourhood with high population density (approximately 42 000/km 2 ), poor sanitation and high burden of enteric disease . CMC has a longstanding relationship with the community, including mapping from previous studies .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Annually, Vellore has a dry season (January – May), a southwest monsoon (June – September), and a northeast monsoon (October – December) [43]. Old Town is a small, low-income urban neighborhood with high population density (approximately 42,000/km 2 ), poor sanitation, and high burden of enteric disease [28, 43]. CMC has a longstanding relationship with the community, including mapping of neighborhood infrastructure (e.g.…”
Section: Methodsmentioning
confidence: 99%